2022
DOI: 10.1038/s41419-022-04601-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of senescence-associated secretory phenotype underlies the therapeutic efficacy of PRC2 inhibition in cancer

Abstract: The methyltransferase Polycomb Repressive Complex 2 (PRC2), composed of EZH2, SUZ12, and EED subunits, is associated with transcriptional repression via tri-methylation of histone H3 on lysine 27 residue (H3K27me3). PRC2 is a valid drug target, as the EZH2 gain-of-function mutations identified in patient samples drive tumorigenesis. PRC2 inhibitors have been discovered and demonstrated anti-cancer efficacy in clinic. However, their pharmacological mechanisms are poorly understood. MAK683 is a potent EED inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 83 publications
3
21
1
Order By: Relevance
“…It has been reported that FBN2 could have excellent diagnostic value for smooth muscle sarcoma and rhabdomyosarcoma [ 70 , 71 ]. Besides, it also has been proved that FBN2 might both have tumor-suppressive effects and is a typical basement membrane marker in several types of cancers [ 72 ]. Previous studies have found that FBN2 harbour cancer-specific promoter methylation in human colorectal cancer [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FBN2 could have excellent diagnostic value for smooth muscle sarcoma and rhabdomyosarcoma [ 70 , 71 ]. Besides, it also has been proved that FBN2 might both have tumor-suppressive effects and is a typical basement membrane marker in several types of cancers [ 72 ]. Previous studies have found that FBN2 harbour cancer-specific promoter methylation in human colorectal cancer [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of EZH2 reduces the repopulation potential of HSPC clones carrying p53 [ 157 ]. Additional mutations in the PRC2 (The methyltransferase Polycomb Repressive Complex 2) Destabilizing PRC2-complex which consists of EZH1, EZH2, SUZ12, and EED subunits, cause cell cycle arrest that overcomes the induction of p53 clonality, and cells exhibit senescence-like phenotypes [ 159 , 160 , 161 ]. In addition, the loss-of-function double mutation of Tp53 and Tet1 (10-11-translocation-1) also induces senescence [ 162 ], illustrating subtle genetic regulation between apoptosis, senescence induction, and clonal proliferation (see Figure 2 ).…”
Section: Hscs Adulthood and Agingmentioning
confidence: 99%
“…31,32 Particularly, MAK683, a derivative of EED226, has entered phase 2 clinical trials to treat lymphomas. 33 In addition, von Hippel−Lindau (VHL) ligandbased EED-targeted PROTAC degraders have also been documented (Figure 1B). The EED-targeted bivalent chemical degrader UNC6852, via recruitment of VHL, selectively degrades EED, EZH2, and SUZ12; impairs the PRC2 catalytic activity; decreases the H3K27me3 levels; and shows antiproliferation in diffuse large B cell lymphoma (DLBCL) cell lines with EZH2-activating mutations.…”
Section: Introductionmentioning
confidence: 97%
“…Regulating the PRC2 activity is a promising anticancer therapeutic strategy, and some compounds including small-molecule inhibitors and proteolysis-targeting chimaera (PROTAC) degraders targeting the PRC2 complex have been reported. , To date, several EZH2 inhibitors have entered clinical development, of which tazemetostat has been approved by the FDA to treat epithelioid sarcoma and follicular lymphoma. , Targeting the protein–protein interactions represents a new paradigm to allosterically regulate the protein functions. , In addition to targeting EZH2, targeting the H3K27me3 binding pocket in EED can allosterically regulate the PRC2 methyltransferase activity and thus represents a novel anticancer strategy. − The development of EED inhibitors has been pursued, and some representative EED inhibitors such as EED226, MAK683, A-395, BR-001, EEDi-5285, and EEDi-5273 are shown in Figure A. These EED inhibitors show strong inhibitory activity against EZH2 inhibitor-resistant cells and also exhibit robust regression of lymphoma xenografts. , Particularly, MAK683, a derivative of EED226, has entered phase 2 clinical trials to treat lymphomas . In addition, von Hippel–Lindau (VHL) ligand-based EED-targeted PROTAC degraders have also been documented (Figure B).…”
Section: Introductionmentioning
confidence: 99%